Pengaruh Struktur Aset terhadap Kebijakan Utang dengan Ukuran Perusahaan sebagai Variabel Moderasi (Studi Empiris pada Perusahaan Sektor Barang Konsumsi Nonprimer yang Terdaftar di Bursa Efek Indonesia Periode 2022–2024) - Putri, Mutiara Angelina; Taufik, Taufeni; Atami, Aulia Pinto (Jurnal Ragam Pengabdian, 2026)
This study examines the effect of asset structure on debt policy, with firm size as a moderating variable, while profitability, liquidity, and growth opportunities serve as control variables. The population comprises Non-Primary Consumer Goods companies listed on the Indonesia Stock Exchange during the 2022–2024 period. Using a purposive sampling technique, 95 companies were selected, yielding 285 firm-year observations. Following outlier treatment, 275 observations were retained for the final analysis, which was conducted using Moderated Regression Analysis (MRA) with SPSS 27. The findings reveal that asset structure exerts a positive and significant influence on debt policy, as companies with a higher proportion of fixed assets tend to rely more heavily on debt financing. Firm size significantly moderates and strengthens this relationship, functioning as a quasi moderator. Among the control variables, liquidity shows a negative and significant effect on debt policy, while growth opportunities exhibit a positive and significant effect, indicating that companies with greater expansion prospects are more inclined to use external debt. Profitability, however, shows no significant impact on debt policy in this sample. These results provide empirical support for Trade-Off Theory and partial confirmation of Pecking Order Theory in the Indonesian non-primary consumer goods sector.